Comparison of nasopharyngeal swab and nasopharyngeal aspiration in adults for SARS‐CoV‐2 identification using reverse transcription‐polymerase chain reaction - Ünsaler, Selin; Okan, Ayşe; Tekin, Süda; Hafız, Ayşenur M.; Gökler, Ozan; Altuntaş, Ozan (Journal of medical virology, 2021)
We aimed to compare reverse transcription‐polymerase chain reaction (RT‐PCR) results of nasopharyngeal aspiration (NA) and nasopharyngeal swab (NS) samples in the diagnosis of coronavirus disease 2019. NS was obtained with a dacron swab and NA was performed by aspiration cannula. The sampling was performed by an otolaryngologist to ensure standardized correct sampling from the nasopharynx. RT‐PCR was performed for the detection of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). The level of agreement between the result of NA and NS samples for each patient was analyzed. The Ct values were compared. Thirty‐three patients were enrolled in the study with a mean age of 56.3 years. Thirteen subjects resulted negative with both NS and NA; 20 subjects resulted positive with NA and 18 subjects resulted positive with NS. The mean values of Ct for NA samples and NS samples were 24.6 ± 5.9 and 24 ± 6.7, respectively. There was no statistical difference between Ct values of NA and NS samples (p = 0.48). RT‐PCR for SARS‐Cov2 performed with NA sample and NS sample showed a strong correlation regarding the positivity/negativity and the Ct values. Highlights The results demonstrated that RT–PCR for SARS–Cov2 performed with NA sample and NS sample showed a strong correlation regarding the positivity and negativity and the Ct values. It is less likely to obtain an insufficient amount of material with NA than that with NS. Therefore, NA may be preferred for the second sampling, especially in patients who are difficult to be sampled with swab because of a septal deviation or patient incompatibility.